2015
DOI: 10.1111/jace.14025
|View full text |Cite
|
Sign up to set email alerts
|

Ga–Sb–S Chalcogenide Glasses for Mid‐Infrared Applications

Abstract: In this study, a novel chalcogenide glass system, Ga–Sb–S, is reported. The glass‐forming ability, the physical properties, and the structure are investigated; and the potential applications of the glasses are evaluated. The compositions consisting of ~3%–10% Ga, ~29%–37% Sb, and ~57%–63% S can form glasses. The glasses have a wide transparent window of ~0.8–14 μm, high linear refractive indices of ~2.62–2.70 (@10 μm), high third‐order nonlinear refractive indices of ~12.4 × 10−14 cm2/W (@ 1.55 μm), low phonon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 22 publications
2
55
0
Order By: Relevance
“…The radiative transition probability is calculated as 276 and 704 sec −1 , respectively37. While in Tm 3+ doped present GaSbS glass, the radiative transition probability of emission at 3.8 μm is about 500 sec −1  21. It shows that different rare earth ions in the same glass system presented on a different radiative transition probability.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The radiative transition probability is calculated as 276 and 704 sec −1 , respectively37. While in Tm 3+ doped present GaSbS glass, the radiative transition probability of emission at 3.8 μm is about 500 sec −1  21. It shows that different rare earth ions in the same glass system presented on a different radiative transition probability.…”
Section: Resultsmentioning
confidence: 94%
“…Recent studies indicated that Ga-based Ga 2 S 3 –Sb 2 S 3 glass systems not only possess good thermal ability but also exhibit higher non-linear susceptibility and Raman gain coefficients, also including the RE (Dy 3+ /Tm 3+ )-doped infrared emissions21222324. In the current work, the Ga composition was tuned in the Sb–S glassy phosphors to find out the trade-off between glass structure and achieving efficient MIR emissions.…”
mentioning
confidence: 92%
“…According to previous research on 80Sb 2 S 3 -20Ga 2 S 3 glass, the broad overlapping peak at about 300 cm −1 is assigned to the [SbS 3 ] pyramid (290 and 314 cm −1 ), the shoulder around 138, 342, and 265 cm −1 to the [GaS 4 ] tetrahedral structure units, and the [S 3 Ga-GaS 3 ] ethane-like unit. 17,29 Gallium tends to be coordinated with sulfur in chalcogenide glasses in fourfold; consequently, [S 3 Ga-GaS 3 ] ethane-like units form to compensate for the shortage of sulfur in the 80Sb 2 S 3 -20Ga 2 S 3 glass 9 . Metal halides, such as AgI, function as a glassy network terminator.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with Se and Te-based ChGes, S-based ones usually have higher power handling ability because of the stronger bonding strength between constituent elements. 1,13 Although the recently developed Ga-Sb-S glasses 14 exhibit remarkably wider IR transmission window and excellent rare-earth solubility, they suffer from crystallization during fiber drawing. However, most S-based ChG fibers have a relatively narrow IR transmission window of ~1-7 µm.…”
Section: Introductionmentioning
confidence: 99%